PAS polyanion hydrogel electrolyte as well as preparation method and application thereof

By synthesizing the electrolytes of polyphonic ion hydraulic hydrogels caused by the free radical aggregation technology caused by heat, the problem of insufficient electrolyte properties of zinc ion batteries, significantly improved the cycle stability and magnification performance of the battery, and extended the service life of the battery.

CN119361858APending Publication Date: 2025-01-24山东孚日鸿硅新材料科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411443081.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The ionic conductivity, cycle stability and rate performance of existing zinc-ion battery electrolytes is insufficient, which limits the battery's efficient energy storage and long cycle life.

Method used

The electrolyte electrolytes of polyphonic ion uterine hydrogels caused by the free radical aggregation technology caused by heat, and a specific combination of single combination and ion exchange response significantly improved the electro -conductivity and mechanical properties of electrolytes.

Benefits of technology

It significantly improves the cycle stability and rate performance of zinc-ion batteries, extends the service life of the battery, and maintains stable performance under different temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361858A_ABST
    Figure CN119361858A_ABST
Patent Text Reader

Abstract

The invention discloses a PAS polyanion hydrogel electrolyte and a preparation method and application thereof, and relates to the technical field of gel electrolytes.According to the scheme, monomers, ZnSO4. 7H2O, kappa-carrageenan, a cross-linking agent and an initiator are added into deionized water, and stirring is performed to form a transparent and uniform precursor mixed solution; injecting the precursor solution into a mold, and carrying out thermal initiation free radical polymerization reaction in a drying oven to form PAS gel; and soaking the PAS gel in a zinc sulfate solution for ion exchange reaction to form the PAS polyanion hydrogel electrolyte. According to the polyanion hydrogel electrolyte prepared by a thermal initiation free radical polymerization technology, the ionic conductivity of the electrolyte and the cycling stability of a zinc ion battery are remarkably improved. The electrolyte shows excellent performance at different temperatures and current densities, so that the battery shows high coulombic efficiency and good reversibility in efficient charging and discharging, the practicability of the zinc ion battery is remarkably improved, and the service life of the zinc ion battery is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gel electrolytes, and in particular to a PAS polyanion hydrogel electrolyte and a preparation method and application thereof. Background Art

[0002] As a new type of energy storage device, zinc-ion batteries have received widespread attention in the field of energy storage in recent years. This technology is based on the need to improve existing battery technology, especially to deal with the potential harm of organic electrolytes to the human body and the shortage of lithium resources. Zinc-ion batteries use zinc as the negative electrode material and realize charging and discharging through the mechanism of ion migration and electron transfer. Their positive electrode materials are usually layered compounds, such as V2O5 and MnO2. These positive electrode materials can effectively embed and extract zinc ions during the charging and discharging process, thereby realizing efficient storage and release of electrical energy. Compared with traditional lithium-ion batteries, the theoretical specific capacity of zinc-ion batteries reaches 820mAh / g. At the same time, due to the abundant and cheap zinc resources, the cost of using this battery is significantly reduced. In addition, the introduction of aqueous electrolytes improves the safety and environmental protection of batteries, making it a more attractive energy storage solution.

[0003] Although zinc-ion batteries have shown many advantages, current technology still has obvious shortcomings. Especially in terms of electrolytes, although traditional zinc sulfate electrolytes have certain ionic conductivity, their ionic conductivity is generally low, which has formed a major obstacle in commercial applications. In addition, although quasi-solid hydrogel electrolytes have attracted attention due to their wide electrochemical window and excellent mechanical properties, their ion mobility is still insufficient compared to liquid electrolytes. This problem not only limits the performance of the battery in high-rate discharge and long cycle life, but may also lead to reduced efficiency and insufficient stability of zinc batteries in practical applications. In addition, the deficiencies of existing polymer electrolytes in ionic conductivity, mechanical strength and thermal stability make them unable to meet the needs of high-performance zinc-ion batteries. Therefore, improving the ionic conductivity and cycle stability of the electrolyte has become a key issue that needs to be urgently solved in zinc-ion battery technology.

[0004] In view of the above technical problems, the present invention aims to provide a method for preparing a polyanion hydrogel electrolyte and its application to solve the problem of insufficient electrolyte performance. Specifically, the present invention successfully synthesized a polyanion hydrogel through thermally initiated free radical polymerization technology, significantly improving the cycle stability and rate performance of zinc ion batteries, thereby significantly extending the battery life. This technological innovation not only provides a new solution for improving the performance of zinc ion batteries, but also lays the foundation for its promotion in a wider range of application scenarios. Summary of the invention

[0005] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a method for preparing a PAS polyanion hydrogel electrolyte, comprising the following steps:

[0006] (1) Preparation of precursor solution: add 20-40 g monomer, 14-24 g ZnSO4·7H2O, and 3-6 g κ-carrageenan to 100 ml deionized water, stir, then add 0.06-0.24 g crosslinker and 0.18-0.8 g initiator, stir to form a transparent and uniform precursor mixed solution;

[0007] (2) injecting the precursor solution prepared in step (1) into a mold, placing a tray, covering the tray with plastic wrap and punching holes, performing a thermally initiated free radical polymerization reaction in an oven, and drying to form a PAS gel;

[0008] (3) The PAS gel is immersed in a zinc sulfate solution to undergo an ion exchange reaction, thereby forming a PAS polyanion hydrogel electrolyte.

[0009] Preferably, in step (1), the monomers are 2-acrylamido-2-methylpropanesulfonic acid and sodium 4-styrenesulfonate, and the mass ratio thereof is (1-3):1.

[0010] Preferably, the cross-linking agent is N,N-methylenebisacrylamide.

[0011] Preferably, the initiator is a persulfate initiator.

[0012] Preferably, the persulfate initiator is ammonium persulfate or potassium persulfate.

[0013] Preferably, in step (1), the stirring is magnetic stirring at a rotation speed of 300-500 rpm.

[0014] Preferably, in step (2), the oven environment temperature is 40-70° C., and the reaction drying time is 100-140 minutes.

[0015] Preferably, in step (3), the concentration of the zinc sulfate solution is 1-3 M, and the soaking time is 6-9 hours.

[0016] The present invention also provides a PAS polyanion hydrogel electrolyte, which is prepared by the above-mentioned preparation method.

[0017] The present invention also provides an application of a PAS polyanion hydrogel electrolyte in a high-conductivity, high-stability and ultra-long cycle zinc ion battery, wherein the PAS polyanion hydrogel electrolyte is prepared by the above-mentioned preparation method.

[0018] The present invention also provides a PAS polyanion hydrogel electrolyte with high conductivity, high stability and ultra-long cycle zinc ion battery, wherein the zinc ion battery is prepared by the following method:

[0019] S1) Preparation of MnVO positive electrode: 0.37 g of vanadium pentoxide is dissolved in 50 mL of deionized water to obtain solution I; 0.17 g of manganese sulfate monohydrate is dissolved in 30 mL of deionized water to obtain solution II; solution I and solution II are placed in a beaker, 2 mL of hydrogen peroxide is added, and the solution is stirred until it turns brick red and then transferred to a 100 mL PTFE hydrothermal reactor and kept at 120°C for 10 hours. The obtained brick red precipitate is washed with deionized water and anhydrous ethanol; finally, it is dried in a vacuum oven at 60°C for 12 hours to obtain a dark green MnVO cathode, and then the MnVO cathode, acetylene black and PTFE with a mass ratio of 6:3:1 are pasted on a titanium foil as a binder, and dried in a vacuum oven at 80°C for 12 hours to obtain a MnVO electrode;

[0020] S2) using the MnVO electrode as the positive electrode, the high-purity zinc sheet as the negative electrode, and the polyanion hydrogel as the electrolyte to prepare a zinc ion battery. The polyanion hydrogel as the electrolyte is prepared by the preparation method of any one of claims 1 to 7.

[0021] Preferably, the zinc foil has a thickness of 0.1-0.2 mm, a diameter of 14 mm, and a purity of 99.99%.

[0022] Preferably, the zinc foil is a CROOD experimental consumable.

[0023] Preferably, the zinc ion battery is a 2032 button cell.

[0024] The monomers selected in the present invention are sodium 4-styrene sulfonate and 2-acrylamide-2-methylpropane sulfonic acid. Through the reasonable proportion and combination of the two monomers, a polymer network structure with negative charge characteristics is formed, which significantly improves the ionic conductivity and mechanical properties of the electrolyte. The network structure can effectively inhibit the charge repulsion between molecules, and by introducing ZnSO4·7H2O, the uniformity of the solution is further improved, creating a good environment for subsequent polymerization reactions.

[0025] The combination of selected monomers and their mass ratio directly affect the performance of polyanion hydrogels. Specifically, this negatively charged polymer network not only improves ionic conductivity and significantly increases the conductivity of the electrolyte, which has significant advantages over traditional zinc sulfate electrolytes, but also enhances the stability and cycle performance of the electrolyte in zinc ion batteries.

[0026] The technical solution of the present invention forms a complete technical closed loop through the preparation of precursor solution, thermally initiated polymerization and ion exchange reaction. The reasonable configuration of the selected monomers makes the polymerization reaction smoother, and the generated polyanion hydrogel has a stable structure and good mechanical properties. The ion exchange reaction further optimizes the performance of the electrolyte and provides a good conductive environment for the charge and discharge process of the zinc ion battery. The overall solution effectively solves the shortcomings of traditional electrolytes in terms of stability, conductivity and mechanical properties through the synergistic effect of various technologies.

[0027] The technical solution provided by the present invention brings beneficial effects:

[0028] First, the polyanion hydrogel successfully synthesized by heat-induced free radical polymerization technology significantly improves the ionic conductivity of the electrolyte. Specifically, the ionic conductivity of the polyanion hydrogel electrolyte prepared by the present invention is as high as 27.02mS / cm, which shows a significant advantage over the traditional zinc sulfate electrolyte. This feature enables the battery to more efficiently migrate ions during the charge and discharge process, thereby improving the overall energy conversion efficiency of the battery.

[0029] Secondly, the polyanion hydrogel electrolyte of the present invention significantly enhances the cycle stability of the zinc ion battery. Experimental results show that the specific capacity of the zinc ion battery using the electrolyte of the present invention is 213 mAh / g at a current density of 1 A / g, and it can stably operate for 1500 cycles, with an average coulombic efficiency of up to 99.93%. This performance improvement ensures the high efficiency and reliability of the battery during long-term use, prolongs the service life of the battery, and overcomes the problem of insufficient electrolyte stability in the prior art.

[0030] In addition, the polyanion hydrogel electrolyte of the present invention performs well in rate performance. Through charge and discharge cycle tests at different current densities, the specific capacity of the battery maintains good reversibility in the range of 0.5 to 4A / g, and the maximum specific capacity can reach 286mAh / g. More importantly, the electrolyte can maintain stable performance even in a wide temperature range of -10 to 80°C. This feature enables the electrolyte of the present invention to perform well under different environmental conditions, providing a strong guarantee for the practical application of zinc ion batteries.

[0031] In summary, the polyanion hydrogel electrolyte of the present invention overcomes many deficiencies in the prior art by improving ionic conductivity, cycle stability and rate performance, and exhibits significant technical effects. These technical effects provide important support for the promotion of zinc ion batteries in high-performance energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is the X-ray diffraction pattern of the polyanion hydrogel electrolyte prepared in Example 1;

[0033] Figure 2 is a scanning electron microscope image of the polyanion hydrogel electrolyte prepared in Example 1;

[0034] Figure 3 is a Fourier transform infrared image of the polyanion hydrogel electrolyte prepared in Example 1;

[0035] Figure 4 The contact impedance diagram of the polyanion hydrogel electrolyte prepared in Example 1;

[0036] Figure 5 is a pressure-displacement diagram of the polyanion hydrogel electrolyte prepared in Example 1;

[0037] Figure 6 is a tensile force-elongation diagram of the polyanion hydrogel electrolyte prepared in Example 1;

[0038] Figure 7 The contact impedance diagram of the hydrogel electrolyte prepared in Comparative Example 1;

[0039] Figure 8 The impedance spectrum of the full battery of the polyanion hydrogel electrolyte prepared in Example 1;

[0040] Fig. 9 The cycle-efficiency & specific capacity curve of the polyanion hydrogel electrolyte prepared in Example 1;

[0041] Fig.10 This is a rate diagram of the polyanion hydrogel electrolyte full battery prepared in Example 1;

[0042] Fig.11 This is a high and low temperature diagram of the polyanion hydrogel electrolyte prepared in Example 1;

[0043] Fig.12 The contact impedance diagram of the polyanion hydrogel electrolyte prepared in Example 3;

[0044] Fig.13 The contact impedance diagram of the polyanion hydrogel electrolyte prepared in Example 4;

[0045] Fig.14 Optical photographs of the polyanion hydrogel electrolyte prepared in Example 1 in the flat (a) and symmetrically folded (b, c) states. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0047] Example 1

[0048] A method for preparing a polyanion hydrogel electrolyte comprises the following steps:

[0049] (1) Pour 10 ml of deionized water into a beaker, and then add 1 g of sodium 4-styrenesulfonate, 1.4 g of 2-acrylamido-2-methylpropanesulfonic acid, 1.6 g of ZnSO4·7H2O, 0.4 g of κ-carrageenan, 0.5% of the monomer weight of N,N-methylenebisacrylamide, and 1.5% of the monomer weight of ammonium persulfate into the beaker and mix well under magnetic stirring at 320 rpm to form a precursor solution.

[0050] (2) Inject the precursor solution prepared in step (1) into a PTFE mold, place an iron plate, seal the iron plate with plastic wrap and pierce holes, perform thermally induced free radical polymerization in an oven at 60° C., remove excess water and dry to form a PAS gel. The reaction drying time is 120 minutes.

[0051] (3) The polyanion hydrogel obtained in step (2) is immersed in a 2M zinc sulfate solution for 8 hours to obtain a polyanion hydrogel electrolyte, which is denoted as PAS.

[0052] The present invention characterized the properties and morphology of the polyanion hydrogel electrolyte prepared in Example 1 by X-ray diffraction and scanning electron microscopy. The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that PAS has no obvious crystal peak, indicating that it has an amorphous structure. Figure 2 The hydrogel structure contains a lot of air. Then the polyanion hydrogel electrolyte was characterized by Fourier infrared analysis. Figure 3 As shown by Figure 3 It can be seen that PAS contains a large number of sulfonate groups. The hydrogel electrolyte prepared in Example 1 was cut with a circular blade of 14 mm in diameter, and 304 stainless steel was used as the cathode and anode to assemble into a symmetrical battery. The contact impedance of the hydrogel electrolyte prepared in this example was tested using the EIS program of the electrochemical workstation (the frequency was set to 100 kHz-100 mHz). The results are as follows: Figure 4 As shown in the figure, it can be seen that the contact impedance of the polyanion hydrogel electrolyte prepared in this embodiment is 1.24Ω; and the ionic conductivity is calculated using formula (1), and the result is 27.02mS cm -1 .

[0053] σ=L / RS (1)

[0054] Where σ represents the ionic conductivity (mS cm-1 ), L represents the thickness of the gel electrolyte (cm), R represents the contact impedance of the gel (Ω), and S represents the contact area between the gel electrolyte and the electrode (cm 2 )

[0055] The present invention uses a universal tensile machine to test the destructive compression test and tensile fracture stress test of the polyanion hydrogel electrolyte prepared in this embodiment. The results are as follows: Figure 5 and Figure 6 As shown in the figure, it can be seen that the maximum compressive stress of the polyanion hydrogel electrolyte prepared in Example 1 of the present invention is 6.79 kN, and the maximum tensile stress accepted is 15.69N.

[0056] Example 2

[0057] A method for preparing a polyanion hydrogel electrolyte comprises the following steps:

[0058] (1) Pour 100 ml of deionized water into a beaker, and then add 10 g of sodium 4-styrenesulfonate, 14 g of 2-acrylamido-2-methylpropanesulfonic acid, 16 g of ZnSO4·7H2O, 4 g of κ-carrageenan, 0.5% of the monomer weight of N,N-methylenebisacrylamide, and 1.5% of the monomer weight of ammonium persulfate into the beaker and mix well under magnetic stirring at 320 rpm to form a precursor solution.

[0059] (2) Inject the precursor solution prepared in step (1) into a PTFE mold, place an iron plate, seal the iron plate with plastic wrap and pierce holes, perform thermally induced free radical polymerization in an oven at 60° C., remove excess water and dry to form a PAS gel. The reaction drying time is 120 minutes.

[0060] (3) The polyanion hydrogel obtained in step (2) is immersed in a 2M zinc sulfate solution for 8 hours to obtain a polyanion hydrogel electrolyte, which is denoted as PAS.

[0061] Example 3

[0062] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to sodium 4-styrenesulfonate was 1:1.

[0063] Example 4

[0064] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to sodium 4-styrenesulfonate was 3:1.

[0065] Example 5

[0066] A method for preparing a polyanion hydrogel electrolyte comprises the following steps:

[0067] (1) 100 ml of deionized water was injected into a beaker, and then 20 g of monomer (the mass ratio of sodium 4-styrenesulfonate to 2-acrylamido-2-methylpropanesulfonic acid in the monomer was 1:1.4), 14 g of ZnSO4·7H2O, 3 g of κ-carrageenan, 0.06 g of N,N-methylenebisacrylamide, and 0.18 g of potassium persulfate were added into the beaker and mixed evenly under a magnetic stirring condition of 300 rpm to form a precursor solution.

[0068] (2) Inject the precursor solution prepared in step (1) into a PTFE mold, place an iron plate, cover the iron plate with plastic wrap and pierce holes, perform thermally initiated free radical polymerization in an oven at 40° C., remove excess water and dry to form a PAS gel, and the reaction drying time is 100 minutes.

[0069] (3) The polyanion hydrogel obtained in step (2) is immersed in a 1 M zinc sulfate solution for 6 hours to obtain a polyanion hydrogel electrolyte, which is denoted as PAS.

[0070] Example 6

[0071] A method for preparing a polyanion hydrogel electrolyte comprises the following steps:

[0072] (1) 100 ml of deionized water was injected into a beaker, and then 40 g of monomer, in which the mass ratio of sodium 4-styrenesulfonate to 2-acrylamido-2-methylpropanesulfonic acid was 1:1.4, 24 g of ZnSO4·7H2O, 6 g of κ-carrageenan, 0.24 g of N,N-methylenebisacrylamide, and 0.8 g of potassium persulfate were added into the beaker and mixed evenly under a magnetic stirring condition of 500 rpm to form a precursor solution.

[0073] (2) Inject the precursor solution prepared in step (1) into a PTFE mold, place an iron plate, seal the iron plate with plastic wrap and pierce holes, perform thermally initiated free radical polymerization in an oven at 70° C., remove excess moisture and dry to form a PAS gel. The reaction drying time is 140 minutes.

[0074] (3) The polyanion hydrogel obtained in step (2) was immersed in a 3M zinc sulfate solution for 9 hours to obtain a polyanion hydrogel electrolyte, which was denoted as PAS.

[0075] Example 7

[0076] A PAS polyanion hydrogel electrolyte in a high conductivity, high stability and ultra-long cycle zinc ion battery, the preparation method of the zinc ion battery is:

[0077] (1) Preparation of MnVO positive electrode:

[0078] Vanadium pentoxide (0.37 g) was dissolved in 50 mL of deionized water under magnetic stirring (solution I); manganese sulfate monohydrate (0.17 g) was dissolved in 30 mL of deionized water under magnetic stirring (solution II); solution I and solution II were mixed in the same beaker, hydrogen peroxide (2 mL) was added, and the solution was stirred until it turned brick red and then transferred to a 100 mL PTFE hydrothermal reactor with a stainless steel shell and kept at 120°C for 10 hours. The obtained brick red precipitate was washed several times with deionized water and anhydrous ethanol; finally, it was dried in a vacuum oven at 60°C for 12 hours to obtain a dark green MnVO cathode, and then 60 wt.% of MnVO cathode, 30 wt.% of acetylene black and 10 wt.% of PTFE were used as a binder (6:3:1); the mixture was pasted on a titanium foil, and the electrode was dried in a vacuum oven at 80°C for 12 hours to obtain a MnVO positive electrode;

[0079] (2) A high-purity zinc sheet was used as the negative electrode, the polyanion hydrogel prepared in Example 1 was used as the electrolyte, and the MnVO positive electrode was used as the positive electrode to prepare a 2032 button cell to obtain a zinc ion battery.

[0080] Comparative Example 1

[0081] The preparation was carried out according to the same preparation method as in Example 1, except that only 2-acrylamide-2-methylpropanesulfonate was added to the monomer in step (1) and mixed evenly, poured into a PTFE mold, placed in an iron plate, covered with plastic wrap and pierced with holes, and placed in an oven at 60 degrees Celsius for 120 minutes to obtain a hydrogel electrolyte, denoted as PA.

[0082] The hydrogel electrolyte prepared in Comparative Example 1 was removed and immersed in a 2 mol / L zinc sulfate solution for 6 hours, and then cut with a circular blade with a diameter of 14 mm, and assembled into a symmetrical battery using 304 stainless steel as the cathode and anode. The contact impedance of the polyanion hydrogel electrolyte prepared in this example was tested using the electrochemical workstation EIS program (with a frequency set to 100 kHz-100 mHz). The results are as follows: Figure 7 As shown in the figure, it can be seen that the contact impedance of the polyanion hydrogel electrolyte prepared in this comparative example is 2.24Ω; and the ionic conductivity is calculated using formula (1), and the result is 15.89mS cm -1 It can be seen that the polyanion hydrogel electrolyte prepared by the present invention has small contact impedance and high ion conductivity.

[0083] The polyanion hydrogel electrolyte prepared by free radical polymerization has good toughness and can resist external deformation, and has high conductivity and can better conduct zinc ions.

[0084] Comparative Example 2

[0085] The preparation was carried out in the same manner as in Example 1, except that the polyanion hydrogel electrolyte prepared in Example 1 was replaced with glass fiber as the (GF-B) separator, and 2 mol / L zinc sulfate (120 uL) electrolyte was perfused.

[0086] The zinc ion batteries prepared in Example 1 and Comparative Example 2 of the present invention were subjected to Nyquist test. The results are as follows: Figure 8 As shown in the figure, it can be seen that the electrochemical impedance of the zinc ion battery made with the hydrogel electrolyte of the present invention is 52.13Ω, while that of the zinc ion battery made with the liquid electrolyte of Comparative Example 2 is 152.7Ω.

[0087] The zinc ion batteries prepared in Example 1 and Comparative Example 2 of the present invention were subjected to cycle-efficiency & specific capacity tests, and the results are as follows Fig. 9 As shown in the figure, it can be seen that the electrochemical specific capacity of the zinc ion battery prepared by the polyanion hydrogel electrolyte of the present invention is 213 mAh g -1 After 1500 cycles, the Coulomb efficiency is 99.93%.

[0088] The zinc ion batteries prepared in Example 1 and Comparative Example 2 of the present invention were tested for battery rate performance. The results are as follows: Fig.10 As shown in the figure, it can be seen that the specific capacities of the zinc batteries prepared by the polyanion hydrogel electrolyte of the present invention are 286, 226, 184, 150, 181, 223, and 278 mAhg, respectively. -1 , showing good reversibility.

[0089] The zinc ion battery prepared in Example 1 of the present invention was tested over a wide temperature range, and the results are as follows: Fig.11 As shown in the figure, it can be seen that it can still work normally and maintain a relatively high capacity at -10 degrees Celsius and 80 degrees Celsius.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PAS polyanion hydrogel electrolyte, characterized in that: The following steps are involved: (1) Preparation of precursor solution: add 20-40 g monomer, 14-24 g ZnSO4·7H2O, and 3-6 g κ-carrageenan to 100 ml deionized water, stir, then add 0.06-0.24 g crosslinker and 0.18-0.8 g initiator, stir to form a transparent and uniform precursor mixed solution; (2) injecting the precursor solution prepared in step (1) into a mold, placing a tray, covering the tray with plastic wrap and punching holes, performing a thermally initiated free radical polymerization reaction in an oven, and drying to form a PAS gel; (3) The PAS gel is immersed in a zinc sulfate solution to undergo an ion exchange reaction, thereby forming a PAS polyanion hydrogel electrolyte.

2. The method for preparing a PAS polyanion hydrogel electrolyte according to claim 1, characterized in that: In the step (1), the monomers are 2-acrylamide-2-methylpropane sulfonic acid and sodium 4-styrene sulfonate, and the mass ratio thereof is (1-3):

1.

3. The method for preparing a PAS polyanion hydrogel electrolyte according to claim 1, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide.

4. The method for preparing a PAS polyanion hydrogel electrolyte according to claim 1, characterized in that: The initiator is a persulfate initiator, and the persulfate initiator is ammonium persulfate or potassium persulfate.

5. The method for preparing a PAS polyanion hydrogel electrolyte according to claim 1, characterized in that: In the step (1), the stirring is magnetic stirring at a rotation speed of 300-500 rpm.

6. The method for preparing a PAS polyanion hydrogel electrolyte according to claim 1, characterized in that: In the step (2), the oven environment temperature is 40-70° C., and the reaction drying time is 100-140 minutes.

7. The method for preparing a PAS polyanion hydrogel electrolyte according to claim 1, characterized in that: In the step (3), the concentration of the zinc sulfate solution is 1-3M, and the soaking time is 6-9 hours.

8. A PAS polyanion hydrogel electrolyte, characterized in that: The PAS polyanion hydrogel electrolyte is prepared by the preparation method according to any one of claims 1 to 7.

9. Application of a PAS polyanion hydrogel electrolyte in a high conductivity, high stability and ultra-long cycle zinc ion battery, characterized in that: The PAS polyanion hydrogel electrolyte is prepared by the preparation method according to any one of claims 1 to 7.

10. A PAS polyanion hydrogel electrolyte with high conductivity, high stability and ultra-long cycle zinc ion battery, characterized in that the zinc ion battery is prepared by the following method: S1) Preparation of MnVO positive electrode: 0.37 g of vanadium pentoxide is dissolved in 50 mL of deionized water to obtain solution I; 0.17 g of manganese sulfate monohydrate is dissolved in 30 mL of deionized water to obtain solution II; solution I and solution II are placed in a beaker, 2 mL of hydrogen peroxide is added, and the solution is stirred until it turns brick red and then transferred to a 100 mL PTFE hydrothermal reactor and kept at 120 ° C for 10 hours. The obtained brick red precipitate is washed with deionized water and anhydrous ethanol; finally, it is dried in a vacuum oven at 60 ° C for 12 hours to obtain a dark green MnVO cathode, and then the MnVO cathode, acetylene black and PTFE with a mass ratio of 6:3:1 are pasted on a titanium foil as a binder, and dried in a vacuum oven at 80 ° C for 12 hours to obtain a MnVO electrode; S2) using the MnVO electrode as the positive electrode, the high-purity zinc sheet as the negative electrode, and the polyanion hydrogel as the electrolyte to prepare a zinc ion battery. The polyanion hydrogel as the electrolyte is prepared by the preparation method of any one of claims 1 to 7.